On the theory of semi-fredholm graphs in topological linear spaces - Vladimirskij, J. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ю. Н. Владимирский. К теории многозначных Ф+-операторов в топологических линейных пространствах. I J. Vladimirskis. Daugiareikšmių Φ+-operatorių topologinėse tiesinėse erdvėse teorijos klausimu